Mechanical behaviour of DNA molecules-Elasticity and migration. - Benke, Matyas; Shapiro, Evgeniy; Drikakis, Dimitris (Elsevier Science B.V., Amsterdam., 2011)
A novel multi-scale simulation method developed to describe mesoscale phenomena occurring in biofluidic devices is presented. The approach combines the macro-scale modelling of the carrier fluid and the micro-scale description of the transported macromolecules or compounds. Application of the approach is demonstrated through mesoscale simulations of DNA molecules. The investigated phenomena include elastic relaxation of dsDNA molecules and migration of ssDNA molecules in a microchannel flow. The results of the first study demonstrate that the elastic behaviour of the DNA molecules can be captured sucessfully. The second study proves that the migration of ssDNA in pressure-driven microchannel flows can be explained by the hydrodynamic interaction with the carrier liquid.